Heterogeneous visible-light-induced Meerwein hydration reaction of alkenes in water using mpg-C3N4 as a recyclable photocatalyst. Issue 2 (12th December 2019) - Wang, Jingjing; Xue, Linshuang; Hong, Mei; Ni, Bangqing; Niu, Tengfei
Abstract : This work developed a visible-light promoted Meerwein hydration reaction by using mpg-C3 N4 as recyclable photocatalyst in aqueous solution. Abstract : A green and efficient visible light induced Meerwein hydration reaction of alkenes in aqueous medium using mpg-C3 N4 as a recyclabe photocatalyst has been disclosed. This protocol provides a direct approach for the preparation of racemic alcohols via a free radical mechanism. Water acted as both a solvent and a reagent without any additives or co-solvents. The metal-free heterogeneous semiconductor is found to be fully recyclable at least 5 times without any significant reduction in activity. The Meerwein hydration reaction has an excellent substrate scope and gave the desired products in moderate to high yields. Furthermore, this reaction could be carried out under solar light irradiation and is applicable for large-scale reactions with satisfactory results.